Strategi Pemasaran UMKM Ikan Sagarurung dalam Meningkatkan Daya Beli di Desa Tanjung Baru Kabupaten Pali Menurut Perspektif Ekonomi Islam - Novita Julianti; Zuul Fitriani Umari; Zulfikri (Economic Reviews Journal, 2025)
This research aims to determine the Marketing Strategy of UMKM in Tanjung Baru Village. The data collection method in this research uses qualitative methods. There are two types of data that researchers use in this research, namely primary data and secondary data. In this research, the data techniques used include observation, interviews and documentation. The respondents in this research were 3 MSME traders of sagar urung fish in Tanjung Baru Village. Based on the results of this research, it can be concluded that the marketing strategy process for sagarurung fish UMKM in Tanjung Baru Village uses social media strategies such as Instagram, WhatsApp and Facebook. The MSME marketing strategy for sagarurung fish in Tanjung Baru village also uses the traveling method. This is done because of the encouragement of daily food needs. To get sagarurung fish, consumers need quite a long time to buy it at the market. Because the market is quite far from residential areas, the idea arose for the MSME Sagarurung fish traders to sell their fish to consumers by getting around using motorbikes or other means of transportation.